Difusi Internet of Things dan Penguatan Hukum dalam Bisnis Berbasis PKM-V (Jurnal Hukum Bisnis Bonum Commune, 2022)
The research objective of Internet of Things Diffusion and Legal Strengthening in Pkm-V-Based Business is to help national development by strengthening the Internet of Things in oyster mushroom cultivation, where this can be a solution to the agricultural land crisis in urban areas in order to continue to realize food security. , then in order to develop more efficient entrepreneurship, oyster mushroom cultivation collaborates with the Internet of things (IoT) in order to keep up with the times, namely the era of the industrial revolution 4.0 which requires that everything can have a connection between tools/machines and humans through the internet network which increases productivity. cultivation and increase profits in entrepreneurship, in addition to development in terms of technology, strengthening in the law needs to be implemented such as Business Licenses and Certificates for Home Industry Food Production and registration of brands to DJKI Ministry of can help business development so that it can compete with n other products, In this study, the author uses an empirical juridical method with a qualitative approach than the results of this study emphasize the importance of multidisciplinary scientific collaboration and innovation in the development of student business based on PKM-V, especially in the Internet of Things technology and strengthening in terms of licensing law. The results of research with a case study of the 2020 PKM-V winner, Bung Partis Cultivator (Bandung Manufacturing Polytechnic) show data that the implementation of the Internet of Things has indeed been able to realize precision agriculture, but the lack of strengthening in terms of law and rampant bureaucratic pathology has made student business based on PKM-V it is difficult to develop and cooperate with partners, therefore deeper socialization is needed regarding legal strengthening in PKM-V as well as improving public services by the government in terms of reducing bureaucratic pathology in the administration of Business Licenses and Home Industry Food Production Certificates.